Characteristics of Commuters’ Single-Bicycle Crashes in Insurance Data. - Utriainen, Roni (MDPI, 2020)
In order to maximize the public health benefits of cycling, the negative impacts of cycling, such as the number and types of crashes, should be identified. Single-bicycle crashes, in which other road users are not collided with, are one of the main safety concerns in cycling, but comprehensive knowledge on these crashes is not available due to poor data sources. This study aimed to identify characteristics of commuters’ single-bicycle crashes in Finland. Firstly, insurance data covering 9268 commuter bicycle crashes in 2016 and 2017 were analyzed to find single-bicycle crashes. The insurance data are based on self-reported crashes. In total, 3448 single-bicycle crashes were found with crash descriptions that were informative enough for investigation of their characteristics. According to the results, 62.9% (95% confidence interval+/−1.6%) of the crashes were related to the infrastructure. In the majority of infrastructure-related crashes, the road surface was slippery. The slippery road surface was typically due to icy or snowy conditions. The lack of proper data complicates the recognition of single-bicycle crashes, and hence policy actions and research projects are needed to develop betterdata sources for proper investigation of cycling safety.
Keywords: Fahrradverkehr; Verkehrssicherheit; Verkehrsunfall; Unfallforschung; Verkehrsforschung; Berufspendler; Datenerhebung; Datenanalyse